Application of the STAD Type Cooperative Learning Model to Improve Cognitive Learning Outcomes in Pancasila Education Subjects for Grade IV Students of SDN Pejagan 5 Bangkalan - Qurrotu Aini; Agung Setyawan; Arnab Dey (Journal of Action Research in Education, 2025)
The aim of this research is to improve student outcomes for students in the Pancasila education subject using a collaborative learning model for students from the student team at SDN Pejagan 5 Bangkalan. The main focus of this research is on revealing the effectiveness of the solving model to increase students' understanding of mutual cooperation and to achieve minimum subject standard achievement (KKM). The method used is Classroom Action Research (CAR) using the Kemmis and McTaggart model. The urban model can significantly improve students' learning outcomes. The students' average score rose to 72.10% in the first cycle, 53.33% in the Prasiclus stage, reaching 86.77% in the Second Cycle, and the proportion of research photos also increased. Based on this, we can draw the conclusion that the urban model effectively improves students' learning outcomes, and teachers to use this cooperative learning model to encourage active and motivation to learn.